Comparison of seoi-nage technique for judo athletes of different skill levels - Ishii, T.; Ae, M.; Koshida, S.; Fujii, N. (ISBS Proceedings Archive (Michigan), 2019)
The purpose of the present study was to compare the biomechanics parameters of seoi-nage in judo between highly skilled judo athletes and skilled ones. The motion data of the seoi-nage were collected on three male elite judo athletes and sixteen male student judo athletes using a three-dimensional motion analysis technique. This study found that the anterior-posterior component of the ankle and hip peak velocity of the tori in turning phase were significantly larger in the highly skilled group than the skilled group. In addition, the peak velocities of the ankle and hip were significantly correlated to the peak angular momentum of the tori. The results suggested that it would be useful for judo coaches to pay a greater attention to linear velocity of the lower extremities to evaluate the seoi-nage skill than the knee extension.